Estimation of longitudinal profile of road surface from stereo disparity using Dijkstra algorithm - Lee, Ki-Yong; Park, Jeong-Min; Lee, Joon-Woong (International journal of control, automation, and systems, 2014)
A novel algorithm capable of estimating the profile of the road surface along the cameraviewing direction is proposed. When a disparity map from stereo matching is given, the algorithm estimates the profile precisely by applying the Dijkstra algorithm to a v-disparity representation. Although the road surface is very changeable, many algorithms of road scene analysis have relied on flatroad assumption or have estimated the profile roughly. The combination of the Dijkstra algorithm and a v-disparity representation contributes to eliminating such assumption and limit. We demonstrated the validity of the proposed algorithm by performing experiments with many road images.